The gaps and environmental challenges for small ruminant production in Turkey - Yildirir M. (Innovation for sustainability in sheep and goats, 2019)
Livestock production aims to sustainability, increasing productivity and producer incomes. In Turkey, largest population of sheep and goat known by adaptation to marginal conditions with low reproductive efficiency, and low milk and wool production In extensive livestock production systems the productivity of meat and milk producing animals is low compared with that of the intensive production systems. There are three general production systems, the sedentary, transhumant and nomadic system. While the nomadic system decline the sedentary system increase and transhumance is still common. Improved genetics is effective in commercial systems, however in marginal environments and extensive livestock systems have interaction effects of the adaptation, production environment and management practices should account for sustainable farming. Breeders prefer cross-breeding and changing their breeds with improved bred to increase productivity (i.e., live weight, milk yield and reproduction). Locally adapted breeds known having lower reproduction, meat and milk production levels’ compared to the exotic breeds and their crossbreds. But, integrated approach should be placed on via developed breeding programs. Breed adaptation, conformity with production environment and marketing opportunity are important points for the sustainable production; therefore interrelated effects must determine and take into consideration in the long-term goals. Good management practices, high exploit production environments, and better product quality for marketing which may answer consumer preferences.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)